Identify the Reality of The Use of The Internet in Technical Measures in the Central Library at the University of Duhok - Haji, Harby H. (Humanities Journal of University of Zakho, 2017)
The current research aims to identify the reality of the use of the internet in technical measures in the Central Library at the University of Duhok through to identify potential services that can be provided by the Internet and get to know the reality of the technical and administrative procedures carried out by the studied library. Has been using the descriptive approach (analytical), also representing the research community Central Library at the University of Duhok and consists of 28 employees, have been distributed (28) complete a questionnaire and retrieval form, has come to a set of search results: An increase in the speed of supply and indexing procedures after the use of the internet. A reduction in costs, and update the information on an ongoing basis and the different artistic yield of use of the network among the staff. Develop future management plans for the development of qualifications and skills of their employees to be able to deal with the technology. The research found a set of recommendations including: The libraries that take advantage of the tools offered by the Internet in terms of helping to develop the library in general and technical procedures in particular activities. Hold lectures, seminars and training courses, workshops, intensive and continuous staff about the use of the Internet in libraries. The need to follow up recent developments in modern information technology.